Reconstructing character education through the Dharma–Prema curriculum: A perspective on education policy - I Ketut Donder; Sandhya Tiwari; I Ketut Wardana; Prasanthy Devi Maheswari; Ni Wayan Jemiwi Jero (Dharmakirti : International Journal of Religion, Mind and Science, 2026)
Background: This study is motivated by structural problems in the implementation of character education in Indonesia, which tends to be normative and instructional in nature and has not yet deeply addressed the dimension of value internalization. A number of studies indicate that the dominant approach to character education remains oriented toward formal compliance, making it less effective in fostering students’ ethical and affective awareness. In this context, this study aims to reconstruct character education through the Dharma-Prema-Based Love Curriculum as a form of policy intervention that integrates the dimensions of moral duty (dharma) and universal love (prema) within a transformative educational framework. Methods: This study employs a qualitative approach using an educational policy analysis design and a descriptive-analytical approach. Data collection techniques involved documentary analysis and phased in-depth interviews, while data analysis was conducted through data reduction, thematic categorization, interpretation of meaning, and the drawing of analytical conclusions, emphasizing the interrelationship between policy issues, curriculum design, and their strategic implications. Findings: The research findings indicate that the Dharma-Prema-Based Love Curriculum possesses the conceptual and practical capacity to address the reductionism of character education by holistically integrating cognitive, affective, and spiritual dimensions. This model strengthens the internalization of values through reflective experiences, ethical practices, and empathetic social relationships, thereby contributing to sustainable character development. Analytically, the research results indicate that the synthesis between dharma and prema provides a stronger normative and practical foundation compared to administrative and fragmentary policy approaches. Conclusion: The study’s conclusion affirms that the reconstruction of character education through the Dharma–Prema Curriculum offers a new strategic direction in Indonesia’s educational policy-one that is more integrative, reflective, and contextual, in supporting human resource development toward Indonesia Emas 2045. Novelty/Originality of this article: The novelty/originality of this article lies in the development of a curriculum model based on the philosophical synthesis of Dharma–Prema as an educational character policy intervention that systematically connects conceptual, normative, and implementational dimensionsm an approach that has not been extensively studied within the context of national education policy.